Development of dynamic load factors for human walking excitation for floor vibration design - Nguyen, Huu Anh Tuan; Lythgo, Noel; Gad, Emad; Wilson, John; Haritos, Nicholas (Zielona Góra: Uniwersytet Zielonogórski)
This paper discusses the derivation of a set of dynamic load factors for calculation of walking response on the basis of measurements made during a biomechanics research carried out with young adults. Firstly, a quite large number of experimental data on single footstep force were collected.
Keywords: walking excitation; step frequency; dynamic load factor; floor vibration; design guide